THE IMPACT OF THE HOTEL INDUSTRY ON THE ECONOMIC GROWTH OF UZBEKISTAN'S REGIONS: ANALYSING THE CONTRIBUTION OF TOURISM INFRASTRUCTURE TO JOB CREATION AND IMPROVED LIVING STANDARDS - Amirova D.A. (University Research Base, 2025)
In the era of globalisation and increasing competition, the hospitality industry is a powerful engine of economic growth. This research examines the impact of the hospitality industry on the regional economies of Uzbekistan. This research considers factors such as job creation, capital attraction, and infrastructure improvements to enhance the standard of living of residents in the region. Specifically, the paper considers the implications of expanding hotel chains and developing tourism infrastructure on regional economic engagement--the rise of small- and medium-sized enterprises, the rise of regional culture initiatives, and improvements to the region's attractiveness to tourists. The study also explores conditions of successful hotel development such as community engagement, marketing, and government support.In the conclusion, the study proposes that in order to realise the sustainable development of Uzbekistan's regions an integrated development framework for the hospitality industry is necessary that considers social and economic factors.